Number of Circulating CD73‐Expressing Lymphocytes Correlates With Survival After Cardiac Arrest. Issue 13 (2nd July 2019) - Ryzhov, Sergey; May, Teresa; Dziodzio, John; Emery, Ivette F.; Lucas, F. L.; Leclerc, Angela; McCrum, Barbara; Lord, Christine; Eldridge, Ashley; Robich, Michel P.; Ichinose, Fumito; Sawyer, Douglas B.; et al.
Abstract : Background: Patients resuscitated from cardiac arrest (CA) have highly variable neurological, circulatory, and systemic ischemia‐reperfusion injuries. After the initial hypoxic‐ischemic insult, a cascade of immune and inflammatory responses develops and is often fatal. The role of the immune response in pathophysiological characteristics and recovery is not well understood. We studied immune cell activity and its association with outcomes in a cohort of CA survivors. Methods and Results: After informed consent, we collected blood samples at intervals over a week after resuscitation from CA. We examined the expression of CD39 and CD73 (alias 5′‐nucleotidase), production of tumor necrosis factor‐α, generation of reactive oxygen species, and secretion of vascular endothelial growth factor by circulating myeloid and lymphoid cells, in comparison to cells obtained from control subjects before coronary artery bypass grafting surgery. The number of circulating total and CD73‐expressing lymphocytes correlated with survival after CA. Incubation of immune cells, obtained from post‐CA subjects, with AMP, a substrate for CD73, resulted in inhibition of tumor necrosis factor‐α production and generation of reactive oxygen species. This effect was blocked by adenosine 5′‐(α, β‐methylene) diphosphate, a specific inhibitor of CD73 and ZM 241385, an A2 adenosine receptor antagonist. We also found that AMP‐dependent activation of CD73 induces production of vascular endothelial growth factor. Conclusions: CD73‐expressing lymphocytes mediate cellular protection from inflammation after CA through inhibition of proinflammatory activation of myeloid cells and promotion of vascular endothelial growth factor secretion. The contribution of CD73 lymphocytes in the regulation of acute inflammation and tissue injury after CA warrants further study.